PENGARUH LATIHAN PLYOMETRIC TERHADAP DAYA LEDAK OTOT TUNGKAI - Ganesa Puput Dinda Kurniawan; Yusuf Nasirudin (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Background: Muscle explosive power is a person's ability to perform as much strength as possible with the effort expended in a short time. The ability of explosive muscle power is influenced by two components: strength and speed. The two components cannot be separated because, in principle, these two components work together to produce explosive muscle power. Methods: This type of research uses a pre-experimental method with a one-group pre-test and post-test design. This study was conducted twice measurements to compare the conditions before and after being given treatment. Results: The paired sample t-test showed p = 0.000, which means there is an effect of plyometric exercise. The conclusion of this study is that there is an effect of plyometric exercise on leg muscle explosive power.